2022
DOI: 10.1038/s41598-022-23639-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the plastid genome of Cratoxylum species (Hypericaceae) and new insights into phylogenetic relationships

Abstract: To expand the genomic information of Hypericaceae, particularly on Cratoxylum, we characterized seven novel complete plastid genomes (plastomes) of five Cratoxylum and two of its allied taxa, including C. arborescens, C. formosum subsp. formosum, C. formosum subsp. pruniflorum, C. maingayi, C. sumatranum, Hypericum hookerianum, and Triadenum breviflorum. For Cratoxylum, the plastomes ranged from 156,962 to 157,792 bp in length. Genomic structure and gene contents were observed in the five plastomes, and were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…However, the chloroplast genome size displayed striking variations among the five Hypericum species. The genome size of T. breviflorum and Cratoxylum cochinchinense, the sister groups of Hypericum, were 167,693 bp and 157,103 bp, respectively [28,29]. These results indicate that the smaller genome size of Hypericum was contracted during the evolutionary process, according to the phylogenetic relationships of Hypericaceae.…”
Section: Genome Size Variations and Gene Lossesmentioning
confidence: 81%
“…However, the chloroplast genome size displayed striking variations among the five Hypericum species. The genome size of T. breviflorum and Cratoxylum cochinchinense, the sister groups of Hypericum, were 167,693 bp and 157,103 bp, respectively [28,29]. These results indicate that the smaller genome size of Hypericum was contracted during the evolutionary process, according to the phylogenetic relationships of Hypericaceae.…”
Section: Genome Size Variations and Gene Lossesmentioning
confidence: 81%
“…When compared to the nuclear-based phylogenetic tree, the molecular placement of I. alba is congruent to that using the complete chloroplast genome sequence; I. alba is also strongly resolved as the species to diverge before I. hederacea , I. purpurea , and I. quamoclit when using the combined dataset of ITS and waxy sequences 14 , and is placed in the same group as I. hederacea , I. indica , I. nil , and I. purpurea , being the first to diverge among the five species under ser. Quamoclit, based on the phylogenetic tree reconstructed using 605 putative single-copy nuclear regions 64 . However, as the clade represented by I. biflora , I. tiliifolia , and I. obscura should contain some other species derived from Argyreiinae 21 , based on the limited sampling size used in this study, we can only verify that I. obscura is grouped with I. tiliifolia when analysed using the ITS sequences based on the finding by Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Blume; C. formosum (Jack) Dyer, ssp formosum ; C. formosum (Jack) Dyer, ssp pruniflorum ; C. maingayi Dyer and C. sumatranum ssp. neriifolium Kurz [ 1 , 2 ]. Accordingly, Juanda et al [ 3 ] reported that the Cratoxylum genus includes six accepted species distributed in Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%